Time, History, and Tradition in the Fundamentalist Imagination. Issue 2 (27th May 2016) - Bendroth, Margaret
Abstract : Fundamentalists—those ministers, theologians, and laymen who joined forces against theological liberalism in the late-nineteenth and early-twentieth centuries—cared deeply about history. In this sense they were no different from other protestants of their age, confronted with a historicized Bible and a world falling into the strict sequential order required by modernity. But fundamentalists were different. They viewed time in categories inherited from American protestant thought, as a logical unfolding of a single beginning rather than as open-ended development. This principle of "first things" lay behind their objections to evolution and biblical criticism, but also their stand on social issues, their insistence that the role of women could and should not progress and change over time. Among evangelicals today, the fundamentalist sense of time as the extension of full and complete beginnings still resonates, in opposition to abortion and homosexuality and in their continuing reverence for the American founding fathers. History can be powerfully immediate. For evangelicals, the Bible is not an ancient text about long-dead people but fully contemporary, and thus read not "literally, " as if every word were true, but as if time did not exist. Ultimately, however, history has no depth or traction, or any theological meaning, a parenthesis between the God-ordained beginning and end of time.